2004
DOI: 10.1007/s00284-003-4076-7
|View full text |Cite
|
Sign up to set email alerts
|

NADP-Glutamate Dehydrogenase Activity Is Increased under Hyperosmotic Conditions in the Halotolerant Yeast Debaryomyces hansenii

Abstract: Glutamate plays an important role in osmoprotection in various bacteria. In these cases, increased intracellular glutamate pools are not attributable to the NADP-dependent glutamate dehydrogenase (NADP-GDH) or the glutamate synthase, which do not increase their activities under hyperosmotic conditions, but rather to changes in other enzymes involved in glutamate metabolism. We performed a study which indicates that, as opposed to what happens in bacteria, the activity of NADP-GDH is fivefold higher when the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 16 publications
4
15
0
Order By: Relevance
“…plantarum DPPMA49 was down‐expressed by low temperature (<13°C) and over‐expressed by NaCl (1·87–5·62%). The same effect of NaCl was also reported for D. hansenii (Alba‐Lois et al. 2004).…”
Section: Discussionsupporting
confidence: 84%
“…plantarum DPPMA49 was down‐expressed by low temperature (<13°C) and over‐expressed by NaCl (1·87–5·62%). The same effect of NaCl was also reported for D. hansenii (Alba‐Lois et al. 2004).…”
Section: Discussionsupporting
confidence: 84%
“…For example, the activity of NADP-glutamate dehydrogenase activity is fivefold higher when the halotolerant yeast Debaryomyces hansenii is grown in the presence of 1 M NaCl [13]. M. varians subsp.…”
Section: Effects Of Different Concentrations Of Nacl On Phytase Produmentioning
confidence: 99%
“…Many results have shown that many enzyme activities in halotolerant yeasts and moderately halotolerant bacteria were enhanced in the presence of NaCl [12][13]. For example, the activity of NADP-glutamate dehydrogenase activity is fivefold higher when the halotolerant yeast Debaryomyces hansenii is grown in the presence of 1 M NaCl [13].…”
Section: Effects Of Different Concentrations Of Nacl On Phytase Produmentioning
confidence: 99%
“…However, this stimulation is weaker than the one observed in S. cerevisiae (André et al, 1991). More recently, the activity of NADPdependent glutamate dehydrogenase has been found to be more sensitive to ionic strength than the corresponding isoenzymes in S. cerevisiae (Alba-Lois et al, 2004). Certainly, not all enzymes of interest have been studied.…”
Section: Salt Tolerance Determinantsmentioning
confidence: 97%
“…They found that among several marine occurring yeast, D. hansenii was the one least affected by high NaCl concentrations Norkrans and Kylin, 1969). Since then D. hansenii has been defined as a halotolerant (Alba-Lois et al, 2004), halophilic (González-Hernandez et al, 2004), or even salt-loving yeast (Silva-Graça et al, 2003), a concept that I will also use in this chapter.…”
Section: Introductionmentioning
confidence: 99%